Central-Local Government Relations in Regional Planning and Budgeting in Indonesia: Between Autonomy and Control - Fatimah, Mira; Haryanto, Haryanto; Dwi Retnandari, Nunuk (Indonesian Association for Public Administration, 2024)
This article analyzes the relationship between central and local governments in regional planning and budgeting policies, while exploring the direction of central government control over regions through regional planning and budgeting policies. The issue of relations between central and regional governments in regional planning and budgeting is finding the right balance between autonomy and control. The research methods used are regulatory content analysis and interviews with policymakers. The results showed that the central government uses planning and budgeting to control the implementation of local government affairs and functions through guidance, detection, coercion, and evaluation of existing regulations. These findings fill the discussion gap regarding central government control of regional governments not only through guidance and supervision but through planning and budgeting policies. This study provides insight into the forms of central government control over regional governments, contributing to the trend of central and regional government relations. The practical benefit of this research is as input in improving regional planning and budgeting system policies for the government.